Worldwide patterns and trends in childhood and adolescent brain cancers, 1990–2021: insights from the global burden of disease study 2021 - Li, Linbo; Cai, Chunhai; Zhao, Qianqian; Fan, Chunsun; Fan, Jian (Frontiers in Public Health, 2025)
BackgroundChildhood and adolescent brain and central nervous system cancers (CABCs) represent the leading cause of cancer-related mortality among individuals aged 0–19 years; however, global trends and socio-demographic disparities remain insufficiently explored.MethodsWe utilized the Global Burden of Disease (GBD) 2021 dataset to evaluate the evolving burden of CABCs across 204 countries from 1990 to 2021. We analyzed age-standardized prevalence rate (ASPR), age-standardized incidence rate (ASIR), age-standardized mortality rate (ASMR), and age-standardized disability-adjusted life years (ASDR) among individuals aged 0–19 years. Methodological approaches, including Joinpoint regression, decomposition analysis, and age-period-cohort modeling, were applied to assess trends across five Sociodemographic Index (SDI) levels. Data robustness was further enhanced through temporal smoothing and adjustments to the mortality-to-incidence ratio for pediatric populations.ResultsGlobally, ASPR exhibited a modest increase (average annual percentage change [AAPC] = 0.42, 95% CI: 0.29–0.54), while ASIR, ASMR, and ASDR demonstrated significant declines (AAPC = −0.29, −1.31, and −1.34, respectively). High-SDI regions experienced the highest ASPR (18.0 per 100,000) and ASIR (2.6 per 100,000), a reflection of advanced diagnostic capabilities and improved survival outcomes. In contrast, Low-SDI regions saw an upward trajectory in both mortality (AAPC = 0.06) and disability-adjusted life years (DALYs) with the burden disproportionately affecting children under 5 years of age. East Asia accounted for the highest burden of cases (63,271 prevalent cases in 2021), while Sub-Saharan Africa exhibited alarming increases in the incidence among young children. Decomposition analysis revealed that the global reduction in DALYs (−498,553) was predominantly offset by population growth and rising prevalence in low-resource settings.ConclusionWhile advancements in medical care have contributed to the reduction of CABC mortality in high-SDI regions, persistent disparities in Low-SDI areas necessitate urgent interventions. Targeted strategies—such as scalable diagnostic tools, establishment of regional treatment hubs, and equitable financial support through global initiatives like the WHO Childhood Cancer Initiative—are crucial to addressing these disparities. This study underscored the dual challenge of enhancing survivorship outcomes in high-income settings while rectifying systemic healthcare gaps in low-resource regions to promote global equity in pediatric oncology care.